Respostas

2014-06-09T15:20:18-03:00
(x+1)² = 4x + 4

x² + 2. x . 1 + 1² = 4x + 4
 x² + 2x + 1 -4x - 4 = 0
 x² - 2x -3 =0      equação de 2° grau

0nde a= 1  b=-2   c=-3

Δ=b²-4.a.c
Δ=(-2)²-4.1.(-3)
Δ=4+ 12
Δ=16  ⇒ raiz de 16 é 4



x'=-(-2) + 4     +2 + 4     6
    ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨=  3
         2.1           2          2 


x"=-(-2) - 4     +2 -4        -2
    ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨= -1                   S:(3, -1)
         2.1          2           2

Bons estudos, abraço.


2014-06-09T15:37:27-03:00
(x+1)² = 4x + 4

x² + 2. x . 1 + 1² = 4x + 4
 x² + 2x + 1 -4x - 4 = 0
 x² - 2x -3 =0      equação de 2° grau

0nde a= 1  b=-2   c=-3

Δ=b²-4.a.c
Δ=(-2)²-4.1.(-3)
Δ=4+ 12
Δ=16  ⇒ raiz de 16 é 4



x'=-(-2) + 4     +2 + 4     6
    ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨=  3
         2.1           2          2 


x"=-(-2) - 4     +2 -4        -2
    ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨= -1                   S:(3, -1)
         2.1          2           2